Concerning the Deactivation of Cobalt(III)‐Based Porphyrin and Salen Catalysts in Epoxide/CO2 Copolymerization. Issue 11 (5th February 2015) - Xia, Wei; Salmeia, Khalifah A.; Vagin, Sergei I.; Rieger, Bernhard
Abstract Functioning as active catalysts for propylene oxide (PO) and carbon dioxide copolymerization, cobalt(III)‐based salen and porphyrin complexes have drawn great attention owing to their readily modifiable nature and promising catalytic behavior, such as high selectivity for the copolymer formation and good regioselectivity with respect to the polymer microstructure. Both cobalt(III)–salen and porphyrin catalysts have been found to undergo reduction reactions to their corresponding catalytically inactive cobalt(II) species in the presence of propylene oxide, as evidenced by UV/Vis and NMR spectroscopies and X‐ray crystallography (for cobalt(II)–salen). Further investigations on a TPPCoCl (TPP=tetraphenylporphyrin) and NaOMe system reveal that such a catalyst reduction is attributed to the presence of alkoxide anions. Kinetic studies of the redox reaction of TPPCoCl with NaOMe suggests a pseudo‐first order in cobalt(III)–porphyrin. The addition of a co‐catalyst, namely bis(triphenylphosphine)iminium chloride (PPNCl), into the reaction system of cobalt(III)–salen/porphyrin and PO shows no direct stabilizing effect. However, the results of PO/CO2 copolymerization by cobalt(III)–salen/porphyrin with PPNCl suggest a suppressed catalyst reduction. This phenomenon is explained by a rapid transformation of the alkoxide into the carbonate chain end in the course of the polymer formation, greatly shortening the lifetime of the autoreducible PO‐ring‐opening intermediates, cobalt(III)–salen/porphyrin alkoxides.